Developing Audio-Visual Arabic Learning Media Based On Islamic Ecotheology For Environmental And Disaster Literacy At Madrasah Aliyah - Ihwan Rahman Bahtiar; Ahmad Marzuq; Muhammad Ridwan Effendi (Tarling : Journal of Language Education, 2026)
Backround - The global ecological crisis and Indonesia’s disaster prone status demand Arabic learning materials that integrate environmental themes and Islamic ecotheology. Current materials, however, rarely address these topics.Urgency of Research - No study has yet designed audiovisual Arabic learning media that deliberately combine Islamic ecotheology (khalifah, amanah, prohibition of fasād) with disaster-mitigation literacy for Madrasah Aliyah students.Research Objectives - This study aims to develop and validate such media to enhance students’ environmental awareness and disaster preparedness.Research Method - A research and development (R&D) design using the ADDIE model was employed, limited to analysis, design, development, and expert validation. The needs analysis involved 203 students and four Arabic teachers from four Madrasah Aliyah in DKI Jakarta and West Java. Data were collected through a validated 42-item questionnaire (Cronbach's Alpha = 0.919), teacher interviews, and expert validation sheets. The media prototype was validated by three experts using a 5 point Likert scale.Research Findings - The highest need dimension was “Desire for audio visual  features” (mean = 3.58; 91.5% agreed), followed by “Necessity of Arabic materials on environment and disaster” (mean = 3.53; 92.1% agreed) and “Integration of Islamic ecotheology” (mean = 3.45; 89.6% agreed). Item level analysis showed that 97.5% of students agreed with P1 (the need for environmental/ disaster vocabulary) and 95.0% with P28 (a preference for animated videos). The developed prototype consists of two episodes (5–7 minutes each) on khalifah and amanah. Expert validation yielded a feasibility score of 88.33% (very feasible).Research Conclusion & Novelty - The media is feasible and directly addresses the identified gap. Its novelty lies in the deliberate integration of Islamic ecotheology values with disaster literacy into a single audio visual Arabic learning medium – a combination absent from previous studies. The prototype can serve as a practical reference for Arabic teachers and curriculum developers seeking to embed ecological and spiritual values into language instruction.